The Deferred African American Dream Depicted in Harlem by Langston Hughes and Lorraine Hansberry's a Raisin in the Sun - Syaila Nur Amaliyah (CV. Publikasi Indonesia, 2024)
This research analyzes how the American Dream is represented and why the depiction of the dream is written as a dream